A record of change in oyster environment through high-resolution geochemical analysis of Late-Holocene sediments from Coastal Ghana - Mahu, E.; Leng, M.J.; Andrews,L.; Englong,A.; Marchant, R. (The Holocen, 2024)
The near-coast environments where oysters occur are among the most impacted by humans globally, especially during the Late-Holocene. Yet, in West Africa, there is no documented historical record of change in these environments. We provide insight into the changing geochemical conditions of two oyster environments through high-resolution analysis of total organic carbon (C), total nitrogen (N), carbon and nitrogen isotope ratios (δ13C, δ15N), and trace elements, in two cores retrieved from the Densu estuary and the Anyanui (Keta) Creek in Ghana. Drastic shifts in sedimentation rate occurred in the Keta and Densu cores around 1996 CE and 960 CE respectively. At these times, comparatively, low levels of C and N were found in the Densu core. Increasing C and N levels and decreasing δ13C upcore aligned with the observed shift in sedimentation rate in the Keta core. The C/N ratios in the Keta core suggest allochthonous organic matter (OM) dominance in the creek. The Densu core showed periodic changes in C/N ratios from very high values (>20) between 1918 BCE and 1321 BCE, to values between 20 and 11 between 1321 BCE and 1977 CE and below 10 from the late 1970s CE to the present day, suggesting a varying degree of transformation in the catchment basin. Extremely high Sulfur (S) and moderate to significant Iron (Fe) increases suggest reducing conditions in the Keta sediments. Moderate Calcium (Ca), Zinc (Zn), and Strontium (Sr) concentrations in the upper part of the Densu core suggest a stronger influence of marine processes in the Densu in recent times. The findings reflect the impacts of catchment basin modification on the health of the two coastal environments, likely to impact the growth, productivity, and sustainability of the fishery of the West African mangrove Oyster.
Research Article
Keywords: land-use/landcover change; marine processes; organic matter